The power characteristics of a lidar transmitter constructed according to the generator-amplifier scheme - Zarudnyi, А.А.; Tsopa, А.I. (Radiotekhnika, 2018)
Technique for calculating the energy characteristics of the lidar transmitter constructed according to the generator-amplifier scheme on an organic dye with a lamp pumping is considered. The results of calculations show that there are optimal ratios of the lengths of the generator and amplifier, at which the effective energy of radiation is maximal.